1977
DOI: 10.1104/pp.59.5.1000
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Has No Effect on Modification of External pH by Soybean Hypocotyl Cells

Abstract: The cellular adjustment of the pH of the external environment of soybean (Glycine mar) hypocotyl elongating cells, frequently assumed to be hydrogen ion secretion when the pH is lowered, is unaffected by auxin. These elongating cells actively adjust the external hydrogen ion concentration (from any pH in the range of 4-8) to pH 5.4 + 0.2. This pH adjustment occurs in a medium which does not contain potassium. Growth-optimum auxin concentrations have no effect on cellular pH adjustment of the external medium, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Addition of auxin after the equilibrium pH had been attained did not alter the pH, but it did increase the rate of elongation, eliciting a normal auxin response. It was concluded that hydrogen ions do not mediate in long term auxin-induced elongation in soybean hypocotyl.The hypothesis that H+ ions act as a second messenger for auxin-promoted elongation (4, 13, 25) is supported by evidence that coleoptile (3,8,10,20,25,26), pea (1,7, 18,19), and soybean (29) segments elongate more rapidly at low pH, Avena and Helianthus wall extensibility is increased at low pH (3, 26), auxin-promoted elongation is preceded by auxin-promoted H+ ion extrusion in Avena (5,6,13,25) (29); (c) after acid-stimulated elongation has subsided, auxin is still capable of increasing the rate of elongation in Avena coleoptile (10, 25, 16) and soybean hypocotyl segments (29); (d) wall-bound glycosidases which have low pH optima, described in support of the hypothesis (16), can be inhibited without inhibiting auxin-promoted elongation in lupin (22) and Avena (9); and (e) auxin does not affect proton secretion in lupin (21) and soybean (28).These data have led us to examine the relationship of HI ionpromoted and auxin-promoted elongation. The accompanying manuscript demonstrates the lack of an auxin effect on medium pH adjustment (28).…”
mentioning
confidence: 69%
“…Addition of auxin after the equilibrium pH had been attained did not alter the pH, but it did increase the rate of elongation, eliciting a normal auxin response. It was concluded that hydrogen ions do not mediate in long term auxin-induced elongation in soybean hypocotyl.The hypothesis that H+ ions act as a second messenger for auxin-promoted elongation (4, 13, 25) is supported by evidence that coleoptile (3,8,10,20,25,26), pea (1,7, 18,19), and soybean (29) segments elongate more rapidly at low pH, Avena and Helianthus wall extensibility is increased at low pH (3, 26), auxin-promoted elongation is preceded by auxin-promoted H+ ion extrusion in Avena (5,6,13,25) (29); (c) after acid-stimulated elongation has subsided, auxin is still capable of increasing the rate of elongation in Avena coleoptile (10, 25, 16) and soybean hypocotyl segments (29); (d) wall-bound glycosidases which have low pH optima, described in support of the hypothesis (16), can be inhibited without inhibiting auxin-promoted elongation in lupin (22) and Avena (9); and (e) auxin does not affect proton secretion in lupin (21) and soybean (28).These data have led us to examine the relationship of HI ionpromoted and auxin-promoted elongation. The accompanying manuscript demonstrates the lack of an auxin effect on medium pH adjustment (28).…”
mentioning
confidence: 69%
“…That is, exogenous auxin should induce just the second response. Since it has previously been shown (17) that acid-induced growth mimics the auxin-induced first response (wall loosening), the experiment was feasible. Segments were excised from the rapidly elongating region of the soybean hypocotyl and mounted directly into the growth-measuring apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…Acidic solutions promote the growth of plant stem (16,21) and coleoptile sections (5,14), but it is not known whether the protons entered the tissues through the cuticle or simply through the cut ends. The inability to detect significant auxin-induced acidification of the external medium with sections of some dicot stems (12,19) where the direction of proton movement is outside to inside, but we have conducted sufficient experiments in which the direction of proton movement was reversed so as to demonstrate that the direction of proton movement has little effect on its conductance (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Vanderhoef et al (19) have pointed out, however, that a low proton conductance of the cuticle has never been demonstrated, and concluded from their studies on intact soybean segments that 'Supported by United States Department of Energy Contract DE-AT06-76ER76019.…”
mentioning
confidence: 99%
See 1 more Smart Citation